A Detailed Analysis of Serious Personal Injuries Suffered by Full Time and Part Time Soldiers of the Australian Army. Issue 3 (28th October 2019) - Schram, Ben; Pope, Rodney; Norman, Adam; Orr, Robin
Abstract: Introduction: The intense training and occupational demands of military personnel place the individual at risk of serious injury. When they do occur, serious personal injuries (SPIs) can lead to medical discharge, mission compromise, and ongoing recurrence of problems. Prior to the implementation of any minimization strategies, an understanding of the causes of SPIs requires development. The aim of this study was to analyze the incidence rates and patterns of SPIs within the Australian Regular Army (ARA) and Australian Army Reserve (ARES). Methods: Data for a 2-year period were obtained through the Work Health, Safety, Compensation, and Reporting database of the Australian Department of Defence. Records of SPIs were extracted, with details including: (a) the activity being performed when the injury was suffered; (b) the body location of injury; (c) the nature of injury; and (d) the mechanism of injury. Results were reported as number of SPIs and converted to SPIs/100 full-time equivalent (FTE) years of service. Results: In total, 507 SPIs were reported over the two-year period (ARA = 466; ARES = 41). SPIs most commonly: occurred during combat training ( n  = 80; 0.13 SPIs/100 FTE years) and physical training ( n  = 66; 0.10 SPIs/100 FTE years); affected the head ( n  = 63; 0.10 SPIs/100 FTE years) and shoulders ( n  = 57; 0.09 SPIs/100 FTE years); and comprised fractures ( n  = 199; 0.19 SPIs/100 FTE years) and soft-tissue injuries ( n  = 103; 0.16 SPIs/100 FTE years). The most common mechanism of injury was falls ( n  = 132; 0.21 SPIs/100 FTE years) or contact with objects ( n  = 114; 0.18 SPIs/100 FTE years). When adjusted for service time, ARES personnel were found to report SPIs more frequently than ARA personnel (0.87 vs. 0.79/100 FTE years, respectively) giving an injury risk ratio (ARA:ARES) of 0.91 [95% CI = 0.66–1.25]. Conclusions: Despite higher absolute numbers of SPIs occurring in ARA, ARES in fact report similar rates of SPIs when adjusted for service time. The natures and mechanisms of SPIs are also similar for both service types and therefore should be the focus of targeted programs to reduce such injuries.